Saintifik dengan bermain air warna di TK Aisyiyah Bustanul Atfal Kajai Kabupaten Pasaman Barat - Sastra Sofia (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
This study used Classroom Action Research conducted in Kindergarten Aisyiyah Bustanul Atfal Kajai. This research was conducted for 2 months, namely as many as 2 cycles, namely cycle I consisted of 3 meetings and cycle II consisted of 3 meetings. Data collection with observation, interviews, and documentation were analyzed by percentage techniques. The results of observations in the initial conditions showed that children's scientific abilities were still low. The implementation of the first cycle of the first meeting to the third shows an increase in children's scientific abilities, but has not yet reached the KKM so that the second cycle is carried out. After the second cycle, the first meeting until the third meeting saw a significant increase in children's scientific abilities, especially in terms of children's abilities. Based on these studies it can be concluded that there is an increase in children's scientific abilities through the Science approach by playing Color Water at Aisyiyah Bustanul Atfal Kajai Kindergarten, Regency of West Pasaman.